The Influence of Brand Trust and Marketing Mix on Customer Satisfaction and its Impact on Customer Loyalty Skincare Skintific in Yogyakarta. - Jeharus, Modesta Orjelina; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine how consumer loyalty is affected by brand trust and the marketing mix. In this study, one hundred respondents made up the sample. A survey approach was employed as the data gathering strategy, while a questionnaire served as the study instrument. The research's test findings made use of the Smartpls 4.1 programs' outer model, inner models, and hypothesis testing. The findings of this study demonstrate that: customer satisfaction influences customer loyalty positively and significantly; brand trust influences customer satisfaction positively and significantly; marketing mix influences customer satisfaction positively and significantly; and brand trust has a positive and significant effect on customer loyalty. Customer loyalty is strongly mediated by customer satisfaction when it comes to the impact of the marketing mix.